Conformational control by intramolecular hydrogen bonding - Luccarelli, J; James W Luccarelli (2013)
Hydrogen bonds are directional, non-covalent interactions between hydrogen and electronegative atoms. Although generally weak, these interactions are critical to the stability of many biological systems including proteins and DNA. This dissertation explores small molecules in which an intramolecular hydrogen bond is the key determinant of conformation. Chapter 1 introduces the protein Grb2 SH3C, details its role in cancer signalling, and delineates the idea of peptidomimetics—small molecules which are functionalized to mimic the structure of a peptide and disrupt protein-protein interactions. Chapter 2 describes a virtual screen for binders to Grb2 SH3C. From a library of 6.3 million compounds, 34 were tested in vitro and two found to bind to the protein in two orthogonal assays. Chapter 3 describes mimics of the polyproline II helix using a benzoylurea scaffold. A small library of these compounds was synthesized and tested for binding to Grb2 SH3C using SPR, a competition assay, and NMR. Chapter 4 describes attempts to mimic a 310 helix using benzamide-based peptidomimetics. The synthesis and in vitro evaluation of these molecules as ligands of Grb2 SH3C is described. Chapter 5 uses quantum chemical calculations to assess the energies of a series of molecular switches. These calculations benchmark a range of modern density functional theory calculations, and attempt to quantify the accuracy of these methods for a large, flexible system. The role of solvation, entropy, geometry, and torsional angles are assessed in accurately calculating the energies of the critical hydrogen bonds.